Pharmacokinetics and Relative Bioavailability of Breviscapine Pills in Human Plasma by HPLC - Bu, Yuehua; Zhao, Min; Bai, Lu; Wang, Miao; Zhao, Ming; Zhang, Xiaodi; Zhao, Chunjie (Asian Journal of Chemistry, 2013)
To evaluate the bioequivalence of scutellarin in breviscapine pills and tablets, the randomized two-way crossover study was conducted in 18 healthy volunteers. After a single dose (containing 160 mg brevisapine), the plasma drug levels were determined by HPLC. By analysis of variance, the main pharmacokinetics parameters of test and reference formulations were followed that tmax were 5.94 ± 0.24 and 6.00 ± 0.0 (h), Cmax were 645.23 ± 48.71 and 599.88 ± 61.19 (ng/mL), t1/2 were 3.68 ± 2.15 and 4.05 ± 2.74 (h), AUC0®24 were 3726.69 ± 700.06 and 3213.94 ± 667.88 (ng/mL·h). The results showed that the two formulations were bioequivalent. The relative bioavailability of the Breviscapin pills was within 117.89 ± 19.16 %.